Prevalence of brucellosis among patients attending Wau Hospital, South Sudan - Madut, Nuol Aywel; Nasinyama, George William; Bwalya Muma, John; Sube, Kenneth L. L.; Ocan, Moses; Muwonge, Adrian; Godfroid, Jacques; Samuel Jubara, Ambrose; Kankya, Clovice (PloS one, 2018)
Brucellosis is a zoonotic disease of public health importance; its prevalence varies globally. In low-income countries, brucellosis is an endemic and neglected disease affecting both animals and humans. This study was intended to establish brucellosis sero-prevalence among patients attending Wau hospital, South Sudan. Across sectional study, was done among randomly selected patients attending Wau hospital. Data was collected using questionnaires and laboratory investigations. Rose Bengal plate Test (RBPT), Serum agglutination test (SAT) and Competitive Enzyme Linked Immuno Sorbent Assay (c-ELISA) was used in the analysis of blood samples serially starting with RBPT which is more sensitive and least specific then SAT. c-ELISA test which is most specific and less sensitive compared to RBPT and SAT was then used to confirm presence of Brucella antibodies in the samples. A total of 416 participants out of 1664 were enrolled to this study. The majority of participants were between 7-to-76 years of age with mean age of 30.72 (SD+/- 12.83). The sero-positivity of patient's blood samples for brucellosis using c-ELISA was 23.3% (97/416) among patients presenting to Wau hospital. Socio-demographic characteristics, occupation, clinical signs of disease and types of animals reared by animal owners showed no significant correlation with occurrence of sero-positivity among patient's blood samples for brucellosis. While ethnicity (Nilotic), knowledge of zoonotic disease, and consumption of animal urine were statistically significant (p<0.05). The study found a high prevalence of brucellosis among febrile patients attending Wau hospital general outpatient clinic. There is need for co-ordination and collaboration between veterinary and health sectors of government to help prevent and control brucellosis in the region.
Keywords: Brucellosis; Patients; Wau Hospital; South Sudan